Deviant behaviour of adolescents as a manifestation of individual anomie: Social and gender aspects of the problem - O. V. Usova; V. V. Usov; N. B. Kostina; T. V. Duran (Russian State Vocational Pedagogical University, 2021)
Introduction. The present paper continues the line of research related to the various forms of anomie in Russian society. In the proposed study, individual forms of anomie manifestation are considered on the example of deviant behaviour of adolescents (students aged 13-17 years old) depending on the gender and mechanisms of its perception by teachers of educational institutions (mental representation of the phenomenon).The aim of the research is to identify the main forms of individual anomie (as deviant behaviour of adolescents) from the standpoint of the teachers' perceptions of student behavior (mental representation of the behaviour of adolescents, depending on the factor of their gender and deviant / prosocial type of behaviour).Methodology and research methods. To obtain sociological data, the following methods were used: questionnaire survey, focused interview, testing. Further, the obtained results were processed by mathematical processing methods (the Fisher analysis of variance (type III SS, polynomial effect)). The influence and interaction of gender factors and the type of deviant/ prosocial behaviour in adolescents (through the mental representation of this phenomenon by teachers of educational organisations) were considered. The current research involved 1643 students aged from 13 to 17 years old and 832 teachers.Results and scientific novelty. As a result of the conducted research, it was determined that the most pronounced forms of deviant behaviour of modern adolescents in the perception of teachers of educational organisations are smoking and absenteeism. This deviant behaviour of adolescents aged 13-17 years old can be considered as the manifestation of individual anomie (in the perception of teachers as "abnormal"). The structure of adolescents' deviant behaviour in the "deviant" group differs more from the structure of adolescents' behaviour in the "prosocial" group. The gender factor of the research participants has a significant impact on the structure of teachers' perception of the behaviour of adolescents in the group of "deviant" and "prosocial" types of behaviour.The scientific novelty of the work lies in the fact that for the first time the authors of the study considered the deviant behaviour of adolescents as the manifestation of individual anomie. Moreover, for the first time, the authors investigated the structure of deviant behaviour of adolescents aged 13-17 years old (with differentiation by gender) and identified the features of the "norm" of behaviour of adolescents in the Russian Federation in the perception of teachers of educational organisations. This allows us to identify the system-forming factors, which influence the attribution of adolescent behaviour to the category of "norm/normality" (as manifestations of anomie), and to consider the mechanisms of teachers' mental representation of the "deviant/prosocial" type of student behaviour, depending on gender.